Student Leadership Involvment - Bailey, Elizabeth; Kinsman, Jacob; Qualley, Anna; Thigpen, Kayla; DuPont, Michael; King, Catherine (My University, 2010)
The purpose of this study was to explore the importance of messages producted by the University of Wisconsin--Eau Claire's Division of Student Affairs to see if there is a relationship between perceptions of the messages and student tendencies to pursue a leadership position.
Organizational Messages and How They Relate to Student Leadership Involvement
Color poster with text and graphs.
Keywords: Universities and colleges--Administration--Communication; College students--Political activity; University of Wisconsin--Eau Claire--Students--Political activity; Student participation in administration--Social aspects; Posters